Use Of 4k Model In Forming 21st Century Skills In Primary Class Students - Meliboyev Anvar Rashidovich (Genius Journals, 2024)
In the article, improving the quality of education, modern education, how a modern teacher should teach a student today, 4K model, 4K skills, updated textbooks of primary classes, effective use of modern methods in lessons issues have been considered.
Keywords: Quality of education; social skills; modern teacher; 4K model